Comparison the impact of IFN-β alone or in combination with vitamin D on critical pathways involved in AML progression - Farzad Nasri; Hassan Jalaeikhoo; Maryam Dadmanesh; Nafiseh Behranvand; Reza Falak; Negin Hosseini Rouzbahan; Yalda Babaei; Khodayar Ghorban (PLoS ONE, 2025)
Background Acute myeloid leukemia (AML) is a malignant disorder characterized by the accumulation of immature myeloid cells which can be developed and exacerbated through inflammation. Interferon-β (IFN-β) and vitamin D (Vit D) are known for their immunomodulatory and anti-proliferative effects. Key molecules like IL-1β, Gal-9, β-catenin, and NF-κB play important roles in AML progression. This study examines the effects of IFN-β alone and in combination with Vit D on U937 cell proliferation and the regulation of these key molecules. Methods Cell counting kit-8 (CCK-8) was applied to assess the effect of IFN-β and Vit D on U937 cells proliferation. Real-time PCR was carried out to evaluate the impact of IFN-β and Vit D on IL-1β, IL-10, Gal-9, β-catenin, and NF-κB genes. ELISA was performed to estimate the protein levels of IL-1β and IL-10. Western-blotting was applied to evaluate the NF-κB signaling pathway. Results The proliferation of U937 cells reduced significantly in the presence of IFN-β, while it did not show a remarkable change following treatment with Vit D. IL-1β gene expression was reduced following either IFN-β or Vit D treatment, while IL-10 gene expression underwent a gentl increase following treatment with IFN-β, which was in contrast to Vit D treatment. IFN-β in contrast to Vit D decreased Gal-9 gene expression. β-catenin gene expression increased after IFN-β or Vit D treatment. NF-κB gene expression reduced following either IFN-β or Vit D treatment, except for the highest concentration of Vit D. At protein level, IFN-β and Vit D treatment leads to a reduction of both IL-1β and IL-10 as well as p-NF-κB. Conclusion Our findings suggest that IFN-β effectively inhibits U937 cell proliferation and modulates key inflammatory and immune-related molecules involved in AML pathogenesis. These results highlight IFN-β as a promising agent for targeting critical pathways in AML and suggest a modulatory, but less potent role for Vit D.